2023
DOI: 10.1097/md.0000000000033006
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for thalamic pain after stroke: A systematic review and meta-analysis

Abstract: Objective: To evaluate the efficacy and safety of acupuncture on thalamic pain after stroke. Methods: The self-established database was searched from 8 Chinese and English databases to June 2022, and the randomized controlled trials articles on the comparative treatment of thalamic pain after stroke with acupuncture were included. That visual analog scale, present pain intensity score, pain rating index, the total efficiency, and adverse reactions were mainly used to evaluate the outcomes. Results: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Meta-analysis showed in 11 trials that acupuncture seemed to be more effective than drugs for treatment of thalamic pain, as assessed by the VAS [mean difference (MD) = −1.06, 95% CI = −1.20 to −0.91, P < 0.00001], the present pain intensity score (MD = −0.27, 95% CI = −0.43 to −0.11, P = .001), the pain rating index (MD = −1.02, 95% CI = −1.41 to −0.63, P < 0.00001), and the total efficiency (RR = 1.31, 95% CI = 1.22 to 1.41, P < 0.00001). 23 Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims. 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…Meta-analysis showed in 11 trials that acupuncture seemed to be more effective than drugs for treatment of thalamic pain, as assessed by the VAS [mean difference (MD) = −1.06, 95% CI = −1.20 to −0.91, P < 0.00001], the present pain intensity score (MD = −0.27, 95% CI = −0.43 to −0.11, P = .001), the pain rating index (MD = −1.02, 95% CI = −1.41 to −0.63, P < 0.00001), and the total efficiency (RR = 1.31, 95% CI = 1.22 to 1.41, P < 0.00001). 23 Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims. 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…Pain after thalamic stroke is a reality that has proven difficult to manage. Meta-analysis showed in 11 trials that acupuncture seemed to be more effective than drugs for treatment of thalamic pain, as assessed by the VAS [mean difference (MD) = −1.06, 95% CI = −1.20 to −0.91, P < 0.00001], the present pain intensity score (MD = −0.27, 95% CI = −0.43 to −0.11, P = .001), the pain rating index (MD = −1.02, 95% CI = −1.41 to −0.63, P < 0.00001), and the total efficiency (RR = 1.31, 95% CI = 1.22 to 1.41, P < 0.00001) 23. Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…A meta-analysis of sleep quality after stroke indicates that poor sleep quality affects 53% of stroke patients. 59 In 2020, a European task force of sleep and stroke researchers emphasized the necessity for clear guidelines to identify, adequately diagnose, and manage sleep disorders in stroke patients, prompting important investigations. 3 The Sleep-disordered breathing in transient ischemic attack (TIA)/Ischemic stroke and continuous positive airway pressure (CPAP) treatment efficacy study conducted by Miano et al 60 reports severe changes of sleep architecture in individuals with stroke or transient ischemic attack, with sleep efficiency and REM sleep being affected the most.…”
Section: Sleep Disorders After Strokementioning
confidence: 99%